Réponses

2014-10-29T11:42:48+01:00
(2/x + 3) - 1/x = 2
(2/x + 3) -1/x x x [<< 1/x fois x] = 2x
(2/x + 3) -1 = 2x
(2/x + 3) - 1 + 1 = 2x + 1
2/x + 3 = 2x + 1
2/x + 3 - 3 = 2x + 1 - 3
2/x = 2x - 2
2x - 2 = 2/x
2x x x [<< 2x fois x] = 2/x x x
2x2 [<< 2x au carre] = 2
2x2/2 = 2/2
x2 = 1
Racine de x au carré = racine de 1
Donc x = 1


Voilà !
je réessaie
d'accord
merci de m'aider
Alors ?
et ça , ça pourrait ? 2x/x(x+3) -( x+3)/x(x+3) =2
2x-x-3/x(x+3)=2
x-3/x(x+3)=2
x-3=2x(x+3)
x-3=2xcarré+6x
2xcarré+5x+3=0
delta=25-24=1
2 solutions : x1=-5-1/4=-6/4=-3/2
et x2=-5+1/4=-4/4=-1